Diagnosing dissent : hysterics, deserters, and conscientious objectors in Germany during World War One - Bennette, Rebecca Ayako, 1973- (Cornell University Press, 2020)
"This book shows how German military psychiatry during World War I allowed for the expression of far more dissent among soldiers than has been recognized"--